Ways to improve the efficiency of wastewater treatment of a cardboard and paper mill - Sablii, Larysa; Zhukova, Veronika; Drewnowski, Jakub (Видавництво Львівської політехніки, 2023)
The results of research on physical and chemical methods for the preliminary treatment of wastewater of a cardboard and paper factory in Khmelnytskyi region of Ukraine are presented. At the cardboard and paper factory, wastewater is treated at a sewage treatment plant, which includes sand traps, primary radial sedimentation tanks, aeration tanks with activated sludge regenerators, secondary radial sedimentation tanks, and bioponds. The use of coagulation and chlorination methods before biological treatment in aeration tanks was proposed. Alumoflock 18% was used as a coagulant, polyacrylamide was used as a flocculant, and sodium hydroxide was used as an alkalizing reagent. The study was conducted on a mixture of industrial and domestic wastewater with COD and BOD5 – 3200 and 1575 mg/dm3, respectively, and on industrial wastewater with COD and BOD5 – 4480 and 1960 mg/dm3, respectively. The effects of reducing COD and BOD5 indicators in the first case after coagulation were 30 and 40%, after chlorination - 37.81 and 43.17%, respectively, in the second after coagulation - 28.57 and 47.24%, respectively. It was established that a significant proportion of organic substances according to the COD indicator is in a dissolved state - 60-70%. It has been proven that as a result of chlorination, the maximum reduction of "pure" COD is achieved, therefore, the possibility and expediency of chlorination of water after the secondary settling tank with increased doses should be considered in the wastewater treatment technology of the cardboard and paper factory.
Keywords: industrial wastewater; cardboard and paper factory; coagulation; alumoflock; chlorination